1995
DOI: 10.1063/1.115366
|View full text |Cite
|
Sign up to set email alerts
|

Lattice location of rare-earth ions in LiNbO3

Abstract: The lattice location of three rare-earth ions (Pr3+, Ho3+, Yb3+) in LiNbO3 is investigated using Rutherford backscattering spectrometry/channeling techniques. All of them are found to occupy the Li+ octahedron but shifted from the Li+ regular position by different amounts (−0.45 Å for Pr3+, −0.38 Å for Ho3+, and −0.3 Å for Yb3+) as previously reported for other rare-earth ions. The amount of displacement is directly related to the variation of the ionic radius of the rare-earth ion, oppositely to transition me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 0 publications
9
66
0
4
Order By: Relevance
“…Rutherford backscattering experiments by Lorenzo et al 19 reported no occupancy of Nb 3+ sites, and our spectroscopy, polarization selection rule properties, and lineshape simulations all appear to be consistent with occupation of only Li + sites. In our experiments, as we shall see, the spectra manifested the basic polarization properties characteristic of the C 3 local symmetry of Li + sites.…”
Section: Methodssupporting
confidence: 61%
“…Rutherford backscattering experiments by Lorenzo et al 19 reported no occupancy of Nb 3+ sites, and our spectroscopy, polarization selection rule properties, and lineshape simulations all appear to be consistent with occupation of only Li + sites. In our experiments, as we shall see, the spectra manifested the basic polarization properties characteristic of the C 3 local symmetry of Li + sites.…”
Section: Methodssupporting
confidence: 61%
“…Furthermore, whereas in many oxide hosts the activator ions occupy well-defined substitutional sites, predictable on the basis of simple arguments based on the charge and the size of the dopant and the substituted ions, this is not the case for all materials. A notable example of this behavior is the non-linear host LiNbO 3 [42], which is of great interest for its ability to generate the second harmonic radiation of the light emitted from Ln 3? ions and for which the Ln 3?…”
Section: Energetics Of the Activator Ions And The Effect And Importanmentioning
confidence: 99%
“…Since LN is a typical nonstoichiometric crystal, it contains specific structural vacancies (i.e., empty oxygen octahedra) [3] and other intrinsic defects in its crystal structure [4,5]. Therefore, various dopants ranging from the H + with valence +1 to the rare-earth cations with valence +3 can be introduced into the crystallographic frame occupying Li sites [6]. This wide range of dopants accounts for the attractive versatility for many important applications [7].…”
Section: Introductionmentioning
confidence: 99%
“…It seems to have become clear that the Li vacancy model is reasonable for describing the defect structure of nonstoichiometric LN single crystals [5], and that dopants prefer to occupy Li sites [6,13]-at least in the low-concentration regime (<6% molar content).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation